Transcranial Direct Current Stimulation of the Dorsolateral Prefrontal Cortex Modulates Cognitive Function Related to Motor Execution During Sequential Task: A Randomized Control Study - Yamamoto, Satoshi; Ishii, Daisuke; Ishibashi, Kiyoshige; Kohno, Yutaka (Frontiers in Human Neuroscience, 2022)
In daily life, we perform a variety of sequential tasks while making cognitive decisions to achieve behavioral goals. If transcranial direct current electrical stimulation (tDCS) can be used to modulate cognitive functions involved in motor execution, it may provide a new rehabilitation method. In the present study, we constructed a new task in which cognitive decisions are reflected in motor actions and investigated whether the performance of the task can be improved by tDCS of the left dorsolateral prefrontal cortex (DLPFC). Forty healthy participants were randomly assigned to a real or sham tDCS group. The anode electrode was placed at F3 (left DLPFC), and the cathode electrode was positioned in the contralateral supraorbital area. Participants underwent one session of tDCS (1.5 mA, 20 min) and a sequential non-dominant hand task was performed for nine trials before and after tDCS. The task consisted of S1 (a manual dexterity task) and S2 (a manual dexterity task requiring a decision). The results showed the S2 trajectory length was significantly shorter after real tDCS than after sham tDCS (p = 0.017), though the S1 trajectory length was not significant. These results suggest that a single tDCS session of the left DLPFC can improve the performance of cognitive tasks complementary to motor execution, but not on dexterity tasks. By elucidating the modulating effect of tDCS on cognitive functions related to motor execution, these results may be used to improve the performance of rehabilitation patients in the future.